Frasa Verba dan Fungsinya pada Berita cnnindonesia.com tentang Affan Kurniawan Terbitan Agustus 2025 - Rani Febriolla De Lima; Mahkota Teja Kusuma; Aprillyana Faza Nur Azizah; Lusia Enjelina Silalahi; Novera Sholicha Nur Armaidah; Asep Purwo Yudi Utomo; Dandung Adityo Argo Prasetyo; Sri Utami Rizki (Lembaga Pengembangan Kinerja Dosen, 2026)
The language used in online news is not only a tool for conveying information but also shapes perspectives that influence readers. One key element in this aspect is phrases. Phrases always appear in various types of text. A phrase is a grammatical unit consisting of two or more words that does not exceed the functional limit and fulfills one of the syntactic functions. Phrases are often found in a text within a sentence, one of which is on the online news page cnnindonesia.com. The type of phrase found in the news page is a verb phrase that functions to form a predicate, link ideas, and better explain the author's intent. The cnnindonesia.com page about Affan Kurniawan published in August 2025 was chosen because it shows a variety of verb phrases that are interesting to study. This study aims to describe the form of verb phrases found in the cnnindonesia.com news about Affan Kurniawan published in August 2025. This research can provide a clearer picture of verb phrases in journalistic texts. The research method used is a qualitative descriptive method. The results of this study describe verb phrases and their syntactic functions in a cnnindonesia.com news story about Affan Kurniawan published in August 2025. This research is useful theoretically and practically. Theoretically, this study enriches the syntactic study of verb phrases and their application in media texts. Practically, the results can serve as a reference for students, researchers, and journalists in using Indonesian effectively and according to the rules.